Grice Maxims Breaking in the Teacher and Students’ Online Interaction - Agnes Lintangsasi Wicaksono; Syafi’ul Anam; Pratiwi Retnaningdyah; Slamet Setiawan (Faculty of Letters, Universitas Abdurachman Saleh Situbondo, 2022)
Grice promotes four maxims to obey as the requirements for successful communication, including quality, quantity, relevance, and manner. However, several conditions require breaking the maxims to make communication more effective, including an interaction between teachers and students. The gender of the students and the practice of online classes also contribute to the breaking of maxims. Hence, this study aims to examine the breaking of Grice maxims in the online classroom interaction between the teacher and students of different genders. The communication between an English teacher and her students in an online class was observed to gather the data. Then, the results were analyzed qualitatively. Finally, this study found that teachers’ interaction with students of both genders produced flouting of quantity maxim. The teacher’s interaction with the female students flouted quantity, relevance, and manner maxims which is caused by the cooperative communication leading females to talk a lot, while the teacher's interaction with male students flouted the quality, relevance, and manner maxims, which is caused by the dominance that males tend to show to female. Moreover, the flouting of maxims made positive and negative results in the communication. Lastly, a more extended period study is suggested to produce further findings.